2008
DOI: 10.1094/mpmi-21-12-1635
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flagellin Perception Mediated by flg22 Receptor OsFLS2 in Rice

Abstract: Plants have sensitive perception systems that recognize various pathogen-derived molecules. We previously reported that rice detects flagellin from a rice-incompatible strain of gram-negative phytopathogenic bacterium, Acidovorax avenae, which induces subsequent immune responses involving cell death. The mechanism of flagellin perception in rice, however, has remained obscure. In this study, we found that flg22, a peptide derived from the flagellin N-terminus, induced weak immune responses without cell death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(149 citation statements)
references
References 30 publications
3
145
1
Order By: Relevance
“…H 2 O 2 detection and quantification H 2 O 2 was monitored by measuring luminol-dependent luminescence ascribable to ferricyanide-catalyzed oxidation according to a previous method described by Takai et al (2008) and Wang et al (2013). Twenty microliters of incubated gametophytes was mixed with 150 μL of 10 mM potassium phosphate buffer (pH 7.8), 20 μL of 14 mM potassium ferricyanide, and 10 μL of 1.1 mM luminol solution; then, the samples were placed in a luminometer (GloMax 20/20, Promega, USA) and analyzed for chemiluminescence immediately.…”
Section: Incubation Experimentsmentioning
confidence: 99%
“…H 2 O 2 detection and quantification H 2 O 2 was monitored by measuring luminol-dependent luminescence ascribable to ferricyanide-catalyzed oxidation according to a previous method described by Takai et al (2008) and Wang et al (2013). Twenty microliters of incubated gametophytes was mixed with 150 μL of 10 mM potassium phosphate buffer (pH 7.8), 20 μL of 14 mM potassium ferricyanide, and 10 μL of 1.1 mM luminol solution; then, the samples were placed in a luminometer (GloMax 20/20, Promega, USA) and analyzed for chemiluminescence immediately.…”
Section: Incubation Experimentsmentioning
confidence: 99%
“…Rice (Oryza sativa) was reported to be insensitive to flg22 . However, recent results showed that flg22 is recognized by rice but that this response is weaker than with full-length flagellin (Takai et al, 2008). A shorter version of the flg22 peptide, called flg15, acts as an antagonist in Arabidopsis (Arabidopsis thaliana), while it is fully active in tomato (Solanum lycopersicum; Meindl et al, 2000;Bauer et al, 2001;Robatzek et al, 2007).…”
Section: Flagellin and Fls2mentioning
confidence: 99%
“…FLS2 is the pattern recognition receptor that mediates plant basal defenses triggered by bacterial flagellin, a microbeassociated molecular pattern (MAMP) (Gó mez-Gó mez and Boller, 2000). The flg22 region within the conserved N terminus of bacterial flagellins carries the elicitation determinant of bacterial flagellin that is recognized by many plants Sun et al, 2006;Robatzek et al, 2007;Takai et al, 2008). FLS2 directly binds flg22 .…”
Section: Introductionmentioning
confidence: 99%